Hubungan Tingkat Pengetahuan dan Sikap Masyarakat dengan Upaya Pencegahan Covid-19 di Mataram - STEFANNY ANGELINE BUDIARTO; HERIN SETIANINGSIH; WAHYU PRASASTI MUTIADESI (HANG TUAH MEDICAL JOURNAL, 2021)
Background : Coronavirus disease 19 is a disease caused by a corona virus which spreads through droplets. The rapid spread of the virus and the increasing incidence of covid-19 must be stopped immediately with specific prevention and handling. The community has a big role to play in preventing Covid-19. A good efforts of prevention really need the role of several factors such as knowledge and attitude. Objective : to analyze the relationship between knowledge and attitude of the community with the effort from preventing coronavirus disease 19 in Cakranegara Selatan village, Mataram City. Method : analytical observation with cross sectional design. The population in this study were people aged 18-40 years who lived in Cakranegara Selatan village. The sampels in this study were 397 people and the sampel was taken using purposive sampling. The instruments used in this study are modified online questionare and already passed validity and reliability test. Bivariate analysis uses the Correlation Spearman’s test with SPSS application. Result : univariate analysis showed 87,4% majority of respondent have good knowledge, 53,4% of respondent have enough attitude and 55,3% of respondent have bad effort of preventing the coronavirus disease 19. The bivariate analysis using Correlation Spearman’s test result found there were a relationship between knowledge and effort of preventing covid-19 with p value=0,000 and a relationship between society attitude and effort of preventing covid-19 with p value=0,000. Conclusion : there is a relationship between knowledge and attitude of the community with the effort from preventing coronavirus disease 19 in Cakranegara Selatan village, Mataram City.